Geometrical and Spectral Properties of the Orthogonal Projections of the Identity - Luis González; Antonio Suárez; Dolores García (Journal of Applied Mathematics)
We analyze the best approximation (in the Frobenius sense) to the identity matrix in an arbitrary matrix subspace ( nonsingular, being any fixed subspace of ). Some new geometrical and spectral properties of the orthogonal projection are derived. In particular, new inequalities for the trace and for the eigenvalues of matrix are presented for the special case that is symmetric and positive definite.